Aquaculture of the New Zealand Geoduck Clam (Panopea zelandica) - Sharma, Shaneel (Auckland University of Technology, 2023)
The geoduck Panopea zelandica has had significant interest from aquaculture New Zealand. To pave the way for the establishment of geoduck aquaculture, information on all areas of geoduck production needs to be determined. The aim of this thesis was to identify conditions and evaluate potential bottlenecks within hatcheries, during transport, and growout. Within hatcheries, much needed information on the successful broodstock conditioning and subsequent larval development was obtained. Investigations into diet ratios of Tisochrysis lutea (ISO) and Chaetoceros muelleri (CM) during the conditioning period revealed important carry over effects. Broodstock that were conditioned on similar proportions of ISO:CM produced embryos that had the highest survival, highest transition into D – veligers, and had the lowest incidence of abnormalities. Fertilization success and embryonic development under different thermal conditions was also explored. Highest rates of fertilization were achieved at the highest temperature (23.7°C) tested. However, there appears to be a thermal maximum for the optimal development of P. zelandica, and embryos were greatly hindered at temperatures >18.5°C due to an increase in cellular blebbing of the developing embryosarising from uneven cell division. Once P. zelandica embryos have transitioned into D – veligers, they remain within the water column for up to 19 days prior to settlement. Therefore, it is no surprise that food availability on its own is a common stressor for the developing larvae. P. zelandica larvae of different ages were subjected to different diet ratios and subjected to acute thermal stress. This study showed that susceptibility of larvae to thermal stress was reduces with increasing larval age, suggesting that older larvae are better able to acquire and store exogenic resources. To establish the crucial link between hatcheries and growout sites, the behavioural and physiological responses during transport and recovery of juveniles was investigated for the first time. The duration of emersion had a clear effect on overall response and recovery. Following 3h of transport, smaller changes within haemolymph osmolality, haemocyte parameters and metabolism were experienced compared to 8h of transport. Also, animal behaviour returned to normal faster within the 3h transport group. Even after 5 days of recovery in standard conditions, the effects of emersion were still evident within the 8h transport group with the use of succinate to fuel the respiratory chain. However, it does appear that given the right conditions and enough food resources, the animals are able to successfully restore internal energy reserves. The final study investigated the potential threat of marine heatwaves to juvenile geoducks within growout sites. This novel study focused on characterising animal behaviour, haemocyte subpopulations, and heat shock protein (hsp79 and hsp90). Geoducks appear to be highly sensitive to the effects of temperature, with animals actively borrowing out of the sediment when temperatures reached 25°C. This was also evident in the haemocyte populations, as there was an increase in the abundance of granulocytes and haemocyte aggregations indicating poor health conditions. However, an increase in the expression of hsp70 does suggest that the animals were actively trying to counter the effect of cellular damage incurred due the thermal strain. In summary, this thesis provides important information on selected factors crucial for the development of aquaculture of P. zelandica in New Zealand.